Nature medicine (Nature America, Inc, 1995)
Abstracts and full-text (PDF only), Sept. 1998- ; abstracts only, Mar. 1996-Aug. 1998.
Keywords: Pathology, Molecular : Periodicals; Molecular biology : Periodicals; Molecular Biology; Medicine; Health & Medicine (General); Molecular biology; Pathology, Molecular; Medizin; Zeitschrift; Online-Ressource